2013
DOI: 10.1590/s0104-11692013000500006
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the implementation of the nursing process in a health area

Abstract: OBJECTIVES: to analyze when the nursing process began to be used in the public and private healthcare centers of Gipuzkoa (Basque Country), and when both NANDA-I nursing diagnoses and the NIC-NOC terminologies were incorporated into this process. METHOD: a retrospective study was conducted, based on the analysis of nursing records that were used in the 158 studied centers. RESULTS: the specific data provided showed that in Gipuzkoa, the nursing process began to be used in the 1990s. As for NANDA-I nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
0
10
0
1
Order By: Relevance
“…Inadequate physical space and materials, besides work overload evidenced as challenges for the implementation of the Nursing Process in this study, are still reported in other similar experiences, constituting threats to the development of the Nursing Process in developing countries (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 50%
“…Inadequate physical space and materials, besides work overload evidenced as challenges for the implementation of the Nursing Process in this study, are still reported in other similar experiences, constituting threats to the development of the Nursing Process in developing countries (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 50%
“…The use of the nursing process in Spanish professional practice started in the 1990s (García‐Carpintero, & Piñón, ; Huitzi‐Egilegor, Elorza‐Puyadena, Urkia‐Etxabe, Esnaola‐Herrero, & Asurabarrena‐Iraola, ; Martín, García, & Asenjo, ). Despite some example of its use at the end of the 1980s (Serrano, Saracíbar, Díaz, Tina, & Narvaiza, ), the utilization of the nursing process was generalized in the 1990s.…”
Section: Resultsmentioning
confidence: 99%
“…The initial use of the NIC-NOC terminologies happened in the first decade of the twenty-first century (Huitzi-Egilegor et al, 2013). But their use has not been as widespread as that of the nursing diagnosis though.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematization of nursing care began in the 1950s with the purpose of joining nursing activities as part of a process and not as isolated actions (1) . It promotes better care quality, providing satisfaction and professional contribution in nursing actions with efficiency and quality (2) .…”
Section: Introductionmentioning
confidence: 99%